개조된 MOCVD 법에 의한 성장 나노 구조 Bi2Te3 열전필름 - 유현우; 정규호; 임주혁; 김광천; 박찬; 김진상 (한국전기전자재료학회, 2010)
Nano structure Bi2Te3 films were deposited on (100) GaAs substrates using a modified MOCVD system and the effect of growth parameters on the structural properties were investigated. Different from conventional MOCVD systems, our reactor consist of pressure control unit and two heating zones ; one for formation of nano-sized particles and the other for the growth of nano particles on substrates. By using this instrument we successfully grow Bi2Te3 films with nano-grain size. The film grown at high reactor pressure has large grain size. On the contrast, the grain size decreases with a decrease in pressure of the reactor. Here, we introduce new growth methods of nano-grain structured Bi2Te3 films for high thermoelectric figure of merit.